Mysticism in handicrafts. Case study: Seljuk Era Pottery - Shojanoori, Nikoo (Revista de la Universidad del Zulia, 2019)
One of the most important periods in Iranian art history in the handicraft part is the Seljuk period. Among the handicrafts of this era, in which diversity and creativity in the motif and structure and quality and quantity of productions are quite noticeable, is pottery art. At the same time, in the pottery of this era, paintings have been used, which are often cryptic and have a certain semantic load. The present study, which is objective and fundamental in terms of method, historical analysis, and gathered information through library resources, after examining the cause of the quantitative and qualitative development of this era of art, has sought to find the reason for the proliferation of the use of mystical motifs in pottery and revealing the meanings of these designs. In this period, when the beginning of changes in the mode of transmission, the mystics and artists express their perceptions of the heart and mind that they did not permit to reveal in the majority of mystical symbols. For example, the attraction of divine love, a kind of relationship and love and lover’s unity, was seen in the form of tales of Layla and Majnun, Yusuf and Zulaikha. But among other influences on the art of this era, the influence of the group’s thoughts, the Brethren of Purity, was on the actions and thoughts of businessmen and craftsmen. According to them, the bothering to construct a craft is a form of cultivation of a worthy soul, and the artifact is a manifestation of the beauty of God. As a result, the artisans of this period, influenced by these thoughts, added as much as possible to the quality and quantity of their work, because they considered the attempt in this way a form of worship, and therefore the transfer of professional skills through a professor to an apprentice student conditioned on having a qualification of that apprentice. In addition, the establishment of large pottery centers in the two major religious and religious cities of Rey and Kashan, which has many mystical circles and monasteries, while also witnessing frequent ethnic and religious conflicts, can also be counted from other influences on the art of this era. Among the Seljuk decorative motif artifacts, Arabesque, geometric and calligraphic motifs are more synchronous with mystical thoughts that have grown more than other motifs and have been used widely. But in the case of potteries dishes, the manuscripts related to lyrical stories and imaginative animal drawings have a larger share, and a number of motifs, such as the motifs of woman, tree, or water which have become more meaningful than the past. Also, the appearance of some motifs to create a new meaning is different from the past, such as the conversion of vertices of letters to human faces.